1983
DOI: 10.1152/ajpregu.1983.244.4.r500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucrose, caffeine, and cola beverages on obesity, cold resistance, and adipose tissue cellularity

Abstract: Rats consuming Coca-Cola and Purina chow ad libitum increased their total energy intake by 50% without excess weight gain. Their resistance to cold was markedly improved. These phenomena were characterized by significant increases in interscapular brown adipose tissue weight (IBAT) (91%), cellularity (59%), triglyceride content (52%), protein content (94%), and cytochrome oxidase activity (167%). In contrast, Coca-Cola consumption did not significantly affect the cellularity or triglyceride content of parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…The consumption of caffeine including coffee, tea and caffeine-rich food was not allowed for at least 2 weeks before the experiment and no sports activities Caffeine is a naturally consumed substance contained in beverages such as coffee, tea, cocoa, and some cola drinks (Bukowiecki et al 1983). It is well established that caffeine increases the human metabolic rate (Yoshida et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The consumption of caffeine including coffee, tea and caffeine-rich food was not allowed for at least 2 weeks before the experiment and no sports activities Caffeine is a naturally consumed substance contained in beverages such as coffee, tea, cocoa, and some cola drinks (Bukowiecki et al 1983). It is well established that caffeine increases the human metabolic rate (Yoshida et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that caffeine increases lipolysis and energy expenditure (13,14) and inhibits hypertrophy of mature adipocytes via suppression of glucose intake (15). Furthermore, it is reported that the intake of a diet containing caffeine reduced the weight of parametrical white adipose tissues in rats (16), and the weight of intraperitoneal adipose tissues in mice (17). To examined the effect of epithelial cells stimulated by caffeine on lipid accumulation in adipocytes, caffeine was added to the apical side of Caco-2 monolayers in a transwell, and 3T3-L1 cells were treated with the permeated basolateral medium, termed caffeine-conditioning medium (CCM).…”
mentioning
confidence: 99%
“…2) CF has also been demonstrated to reduce the weight of adipose tissues in experimental animals fed with a normal diet. For instance, Bukowiecki et al 3) have reported that the intake of 0.057% and 0.2% of CF for 9 weeks both reduced the weight of parametrial white adipose tissues in rats. Chen et al 4) have shown that a CF intake (4 mg/ day) for 4 weeks decreased the weight of body fat in genetically obese mice, and Michna et al 5) have reported that the ingestion of 0.04% CF for 15 weeks decreased the weight of the parametrial fat pad by 43% in mice.…”
mentioning
confidence: 99%
“…These results show that the CF intake suppressed the accumulation of body fat. There have been several reports on the antiobesity action of CF alone under the condition of a normal diet by Zheng et al, 6) who showed that a 0.05% CF intake reduced the weight of intraperitoneal adipose tissues in mice, and by Bukowiecki et al, 3) who reported that 0.057% CF decreased the weight and triglyceride content of parametrial white adipose tissues in rats. The results of the present study show that even 0.025% CF, which corresponds to the daily intake of CF that is contained in tea and coffee, had an anti-obesity effect under the influence of a high-fat diet.…”
mentioning
confidence: 99%